A terahertz-driven non-equilibrium phase transition in a room temperature atomic vapour - Wade, C.G.; Marcuzzi, Matteo; Levi, Emanuele; Kondo, J.M.; Lesanovsky, Igor; Adams, C.S.; Weatherill, K.J. (Nature Publishing Group, 2018)
There are few demonstrated examples of phase transitions that may be driven directly by terahertz-frequency electric fields, and those that are known require field strengths exceeding 1 MVcm−1. Here we report a non-equilibrium phase transition driven by a weak ( 1 Vcm−1), continuous-wave terahertz electric field. The system consists of room-temperature caesium vapour under continuous optical excitation to a high-lying Rydberg state, which is resonantly coupled to a nearby level by the terahertz electric field. We use a simple model to understand the underlying physical behaviour, and we demonstrate two protocols to exploit the phase transition as a narrow-band terahertz detector: the first with a fast (20μs) nonlinear response to nano-Watts of incident radiation, and the second with a linearised response and effective noise equivalent power (NEP) ≤1 pWHz−1/2. The work opens the door to a new class of terahertz devices controlled with low field intensities and operating in a room-temperature environment.